Effect of nitrogen fertilization and shading on morphogenesis, structure and leaf anatomy of Megathyrsus maximus genotypes - Lopes, Aline da Rosa; Lage Filho, Nauara Moura; do Rêgo, Aníbal Coutinho; Domingues, Felipe Nogueira; Silva, Thiago Carvalho da; Faturi, Cristian; Silva, Naiara Caixeta da; da Silva, Wilton Ladeira (Frontiers in Plant Science, 2024)
The use of exotic grasses of African origin for pastures in Brazil has been a major advancement in livestock production, but little is known about the responses of these grasses to nitrogen fertilizers associated with shading. In this study, the morphogenetic, structural, and leaf anatomical characteristics of Megathyrsus maximus cultivars’ Tamani and Quênia were investigated as a function of N dose and shade. Morphogenetic and structural characteristics and leaf anatomy were studied under three shading levels (0, 30, and 50 %) and four N doses (0, 100, 200, and 300 kg N ha-1) to simulate growth in a silvopastoral system. When comparing the cultivars, Quênia was more efficient in terms of phyllochron up to fertilization with 100 kg N ha-1. The leaf senescence rate of Tamani was higher than that of Quênia at the 30 and 50 % shade levels. The total area (TA) occupied by leaf tissues decreased in Quênia as a function of the increase in N fertilization, whereas the TA of Tamani did not change. The thickness of the adaxial epidermis was greater in Quênia (0.68 µm) than in Tamani (0.50 µm) when not fertilized. The area occupied by the mesophyll was greater in both cultivars when they received fertilization equivalent to 300 kg N ha-1. Quênia grass has a smaller phyllochron than Tamani grass, due to the rapid reconstruction of its photosynthetic apparatus, especially when it receives higher levels of nitrogen fertilization. However, Tamani grass has a greater distribution of plant tissues. The mesophyll area is larger in Tamani grass due to the greater presence of chloroplasts, which facilitates digestion by animals. The Tamani modified the leaf anatomical tissues more significantly in relation to shading, whereas the Quênia modified them in relation to N fertilization, which reinforces the suggestion of a more appropriate use of Tamani in silvopastoral systems.